Breakdown of Arabidopsis thaliana thioredoxins and glutaredoxins based on electrostatic similarity-Leads to common and unique interaction partners and functions. - Yana Bodnar; Manuela Gellert; Faruq Mohammed Hossain; Christopher Horst Lillig (PLoS ONE, 2023)
The reversible reduction and oxidation of protein thiols was first described as mechanism to control light/dark-dependent metabolic regulation in photosynthetic organisms. Today, it is recognized as an essential mechanism of regulation and signal transduction in all kingdoms of life. Proteins of the thioredoxin (Trx) family, Trxs and glutaredoxins (Grxs) in particular, catalyze thiol-disulfide exchange reactions and are vital players in the operation of thiol switches. Various Trx and Grx isoforms are present in all compartments of the cell. These proteins have a rather broad but at the same time distinct substrate specificity. Understanding the molecular basis of their target specificity is central to the understanding of physiological and pathological redox signaling. Electrostatic complementarity of the redoxins with their target proteins has been proposed as a major reason. Here, we analyzed the electrostatic similarity of all Arabidopsis thaliana Trxs, Grxs, and proteins containing such domains. Clustering of the redoxins based on this comparison suggests overlapping and also distant target specificities and thus functions of the different sub-classes including all Trx isoforms as well as the three classes of Grxs, i.e. CxxC-, CGFS-, and CC-type Grxs. Our analysis also provides a rationale for the tuned substrate specificities of both the ferredoxin- and NADPH-dependent Trx reductases.